Contextual Action Theory in Nursing - Valach, Ladislav (Journal of Clinical and Practical Nursing, 2019)
After pointing out the wide scope of issues in nursing and summarizing some of the attempts in nursing to deal with this problem of wide scope we propose a conceptual consideration to address this issue anew. We suggest that the contextual action theory is well equipped to provide an economical and concise way of integrating various approaches and disciplines as well as different tasks a nursing conceptualization has to address, particularly in dealing with the issue of practice. We describe what action is, how it could be seen as a system and how it could be useful in nursing practice. Specifically, we detail the application of the contextual action theory in devising nursing procedures, in providing theories and research methods in nursing research and in evaluation processes in nursing. In addressing some limitations of the suggested approach, we stress that it is not a theory of everything and that it does not deliver ready-made instruments for obtaining quantitative data.
Keywords: Nursing; action theory